Mi querido Mijael - Oz, Amos (Biblioteca Amos Oz (Ediciones Siruela), 2015)
As the years pass and Hannah's tempestuous fantasy life encroaches upon reality, she feels increasingly estranged from him and the marriage gradually disintegrates. This novel is at once a haunting love story and a reflective portrait of place.